Legal Defects Of Sale And Purchase Deeds: A Review Of The Responsibilities Of Officials Making Land Deeds In Indonesia - Magistasari, Elvina; Sentot Sudarwanto, A.L.; Harahap, Burhanudin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
This research discusses legally defective sale and purchase deeds and the responsibilities of Land Deed Drafting Officials (PPAT) in Indonesia. Land is a vital element for fulfilling human needs, and land certificates as proof of ownership are very important in the agrarian legal system. The land buying and selling process must be carried out in accordance with legal provisions so that the resulting sale and purchase deed (AJB) has valid legal force. PPAT, as the official who has the authority to make authentic deeds, must ensure the validity of the documents and the completeness of the legal process when making AJB. Making AJB that meets formal and material requirements is very important; otherwise, legal defects may occur that result in PPAT's liability. This article examines the sanctions that can be imposed on PPAT if there are errors, both in administrative, civil and criminal contexts, in accordance with applicable laws and regulations. This research uses the nature of normative juridical research to analyze PPAT accountability and expand understanding of practices that are in accordance with law and professional ethics. The results show that PPAT has a big responsibility in maintaining the validity of deeds, and violations of legal procedures can result in serious sanctions, both administrative and criminal.